2023
DOI: 10.3892/etm.2023.11849
|View full text |Cite
|
Sign up to set email alerts
|

Icariin protects cerebral neural cells from ischemia‑reperfusion injury in an in vitro model by lowering ROS production and intracellular calcium concentration

Abstract: Ischemia is one of the major causes of stroke. The present study investigated the protection of cultured neural cells by icariin (ICA) against ischemia-reperfusion (I/R) injury and possible mechanisms underlying the protection. Neural cells were isolated from neonatal rats and cultured in vitro. The cells were subjected to oxygen-glucose deprivation and reoxygenation (OGD-R) as an I/R mimic to generate I/R injury, and were post-OGD-R treated with ICA. Following the treatments, cell viability, apoptosis, reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 74 publications
0
1
0
Order By: Relevance
“…Subsequent blood reperfusion process will lead to massive production of ROS and further expand the damage. A previous study demonstrated that ICA protects cerebral neural cells from I/R injury by lowering ROS production and intracellular calcium concentration(Ning and Gao 2023 ). Here in, we established an in vitro oxidative damage model by treating PC-12 cells with 200µM H 2 O 2 for 8 h. After pre-treatment with ICT, the mortality rate of model cells was reduced, while the intracellular ROS level was significantly decreased, indicating that ICT is a potential therapeutic drug for alleviating oxidative damage.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent blood reperfusion process will lead to massive production of ROS and further expand the damage. A previous study demonstrated that ICA protects cerebral neural cells from I/R injury by lowering ROS production and intracellular calcium concentration(Ning and Gao 2023 ). Here in, we established an in vitro oxidative damage model by treating PC-12 cells with 200µM H 2 O 2 for 8 h. After pre-treatment with ICT, the mortality rate of model cells was reduced, while the intracellular ROS level was significantly decreased, indicating that ICT is a potential therapeutic drug for alleviating oxidative damage.…”
Section: Discussionmentioning
confidence: 99%